Problem Solving Ability Of Perspective Pre Teacher: A Pisa On Uncertainty And Data Content - Dede Suratman; Edy Yusmin; Nadya Febriani Meldi; Ahmad Yani T (STKIP Singkawang, 2025)
International standard evaluation, PISA, one of which tests problem solving and literacy skills in the Uncertainty and data content on the topic of statistics, until now Indonesia is still below the OECD average. This study is here to describe how the ability of prospective teachers in problem solving is based on the Polya stages. This research needs to be done, where students who will become teachers should have national and international standardized abilities so that Indonesian education can compete globally. The method used in this study is descriptive qualitative which describes the problem solving of the research subjects based on the Polya steps, namely understanding the problem, making a plan, implementing the plan and looking back. The work data from the PISA question instrument that has been adapted, modified according to the surrounding culture and has been validated by experts. In addition, the interview technique was carried out based on interview guidelines developed from the indicators of each Polya step. The research subjects were semester VII students who were selected based on the fulfillment of a greater credit load which could provide definite information on the output of prospective educators in the future. The results of the study showed that from the 4 Polya steps of the 4 questions analyzed, it was found that high group students had very good problem solving. Meanwhile, the students in the medium group are divided into two categories, one is almost at low ability and the other is in the medium group. One sample of the medium group has moderate obstacles in step 2 for questions 2 and 4 and the other is only constrained by number 2. For the low group, it is almost similar to the medium group, the difference lies in the implementation of steps 2,3 and 4 on polya which are incomplete except for number 4.